Three new species of crustose Physciaceae from Guatemala, with notes on some additional species - Giralt, Mireia; Boom, Pieter P. G. Van Den; Mayrhofer, Helmut; Elix, John A. (Phytotaxa, 2014)
Three crustose species of Physciaceae from Guatemala are reported as new to science, the saxicolous Buellia rugosissima and Dimelaena subsquamulosa and the corticolous Sculptolumina conradiae. Detailed descriptions of these species are presented together with notes on their chemistry, distribution, ecology and taxonomy. Additional information is given for a further ten species of Physciaceae, nine of which are new records for the country.